The supervisory recognition of netting for capital adequacy purposes : consultative proposal - Basel Committee on Banking Supervision; Bank for International Settlements (Basle Bank for International Settlements, 1993)
This consultative report proposes that the 1988 Capital Accord should be revised to recognise, in addition to netting by novation, other forms of bilateral netting of credit exposures to the extent that such arrangements are effective under relevant laws and comply with the other minimum standards set forth in the Lamfalussy Report interbank netting schemes, published by the BIS in November 1990
other title : Proposal for a change in the supervisory recognition of netting under the 1988 capital accord
Keywords: International banking; INTERNATIONAL BANKING; MANAGEMENT; FINANCIAL MANAGEMENT; RISK MANAGEMENT